2015
DOI: 10.7454/psr.v2i3.3483
|View full text |Cite
|
Sign up to set email alerts
|

Sintesis dan Karakterisasi Hidrogel Superabsorben Kitosan Poli(N-Vinilkaprolaktam) (Pnvcl) Dengan Metode Full IPN (Interpenetrating Polymer Network)

Abstract: AbstrakMaterial polimer untuk menyusun hidrogel harus dapat mengembang (swell) dan mempertahankan fraksi air pada strukturnya, namun tidak larut dalam air. Polimer alami memiliki gugus fungsi yang dapat menjadi pusat aktif reaksi dimana dapat dilakukan modifikasi untuk menghasilkan suatu polimer dengan karakteristik yang lebih baik. Kitosan merupakan polimer alami yang memiliki kekuatan struktur yang kurang dibandingkan kemampuan mengembang. Sintesis hidrogel kitosan dengan metode full interpenetrating polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
5
0
2
Order By: Relevance
“…The process of water molecules entering the gel structure will enhance the diffusion of the active ingredients from the chewable gummy. The larger and faster the ability of the matrix to expand, the faster the release of Moringa leaf extract from the preparation occurred [39]. The results of statistical analysis of the swelling ratio parameters showed that there were significant differences between the four formulas (p<0.05).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The process of water molecules entering the gel structure will enhance the diffusion of the active ingredients from the chewable gummy. The larger and faster the ability of the matrix to expand, the faster the release of Moringa leaf extract from the preparation occurred [39]. The results of statistical analysis of the swelling ratio parameters showed that there were significant differences between the four formulas (p<0.05).…”
Section: Resultsmentioning
confidence: 95%
“…swelling ratio test aims to see the swelling ability of the carrier. The greater and faster the swelling capacity of the carrier, the faster the dissolving time, hence the release of the active ingredient from the dosage form is also faster [28]. The swelling ratio test was carried out by weighing the dry chewable gummy tablet, the preparation was then immersed in 100 ml ± 10 seconds of water to obtain the wet weight.…”
Section: Swelling Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Hidrogel merupakan jaringan polimer tiga dimensi dengan kemampuan menyerap air pada ruang antar molekul tanpa merubah struktur polimer tersebut (Wivanius & Budianto, 2015). Bahan hidrogel dapat berasal dari polimer alam, sintetik atau kombinasi keduanya yang disintesis melalui reaksi cross-linking.…”
Section: Pendahuluanunclassified
“…We measured the initial weight (Wi) and dry weight after immersing (Wa) during the process. After that, we calculated all quantities to obtain Degree of Crosslinking (DC) (Wivanius & Budianto, 2015) and Degree of Degradation (DD) (Capanema et al 2018) by using equation ( 1) and (2).…”
Section: Degree Of Crosslinked and Degradationmentioning
confidence: 99%